Framing the Trial of Binayak Sen: The Intersection of Procedural Justice, Distributive Justice, Legitimacy, and Collective Action Framing - Smith-Jones, Siobhan E.; Leichty, Greg; Margaret U. D’Silva; Meyer, Nicole L. (Intercultural Communication Studies, 2026)
Framing the Trial of Binayak Sen: The Intersection of Procedural Justice, Distributive Justice, Legitimacy, and Collective Action Framing